Baseline concentrations of pharmaceuticals in Kuwait's coastal marine environment. (December 2021) - Gevao, Bondi; Uddin, Saif; Dupont, Sam
Abstract: This study was carried out to provide baseline information on the concentrations of pharmaceuticals in Kuwait's coastal waters. Samples were collected over four sampling campaigns from various outfalls that occasionally discharged water into the marine environment and analyzed for a range of pharmaceuticals including analgesic/anti-inflammatories, antibiotics, anticoagulant, antidiabetic, antihelmintics, antihypertensives, antiplatelet agent, asthma medication, β-blocking agent, calcium channel blocker, diuretic, histamine H1 and H2 receptor antagonist, lipid regulators/cholesterol-lowering, prostatic hyperplasia, psychiatric drug, sedation and muscle relaxant, synthetic glucocorticoid, tranquilizer and x-ray contrast media. The levels varied between the detection limits of the method and a maximum of 28, 183 ng/L for analgesics/anti-inflammatories. The highest pharmaceutical concentrations were in samples collected during the September campaign, possibly linked to the increased prescription of these medications to treat infectious diseases and flu prevalent in Kuwait during the winter months. The spatial variation is concentration is evident with KISR site being most polluted as hospital wastewater is discharged at the site. This study provides the first dataset on the concentrations of pharmaceuticals in the seawater in Kuwait and possibly the wider Arabian Gulf. Kuwait's coastal water pharmaceutical concentrations derived from this study exceed those reported from the Spanish coast, the Hong Kong harbour, the Bohai and the Yellow seas. More studies are needed to evaluate the environmental impact that these residues may have on non-target organisms. Highlights: First ever report on concentrations of pharmaceuticals in Kuwait coastal waters Most of the pharmaceuticals were detectable in seawater. Elevated levels of analgesic, antibiotics, anti-histamine concurs with flu season.